Typology and Resolution of Core-Plasma Partnership Conflict in Shrimp Farming - Siahaan, Flora Meliana; Amalliah (Jurnal Sosial Humaniora, 2025)
The core-plasma partnership conflict between companies and shrimp farmers in Bumi Dipasena, Lampung, represents the complex socio-economic dynamics within the fisheries sector. This study aims to identify the root causes of the conflict and map out the typology of the resolution strategies that have been applied. Using a literature review approach, the analysis focuses on aspects of power relations, transparency, and government intervention. The findings indicate that the conflict was triggered by breaches of agreement, lack of corporate accountability, and unequal access to resources. The typology of resolution includes legal approaches, mediation, and community empowerment efforts through shrimp farmers' organizations. This study highlights the importance of conflict communication and multi-actor engagement in achieving fair and sustainable resolution.